O zachowaniu się przy stole, czyli kodeks etyki biesiadnej w „Uczcie” Filoksenosa na tle greckiej tradycji literackiej - Stuligrosz, Magdalena (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza, 2008)
The author of the article presents Greek sympotic and dining customs mentioned by Philoxenus of Leucas in his poem Deipnon in comparison with the archaic and classical model of sympotic behaviour. She shows the importance of moderation and balance not only in consumption of food and wine but also in various aspects of entertainment contained within the symposium part of the meal.

Philoxenus of Leucas in his poem entitled Deipnon (Banquet) mentions various dining and sympotic customs and practices that accompanied the consumption of meal and wine. Some of them, like excessive consumption of food and distribution of lavish and elaborate meal, refect “the life of luxury” or “the experience of pleasure”, which developed in the Greek world from the end of the ffth century onwards. But most of the activities described by Philoxenus (washing hands before meal, garlands, libation of wine offered to various gods) were ordered by ritual and attested by archaic tradition. In archaic lyric and elegy there is emphasis on moderate drinking (according to the principle of mštron) required to perform feats of balance, based on mental or physical agility. Philoxenus also concentrates on the various aspects of entertainment provided in the symposium part of the meal – toasting of friends, conversation, riddles, competition in poetic performances and party games. His description of symposium refects the idea rooted in the Greek literature of archaic and classical period, according to which the main aim of banquet was not simply consumption of food and wine, but achieving mental pleasure through intellectual activities and cultural refection. This kind of pleasure was available only to well-behaved symposiasts, who were inspired by drinking wine mixed with water to a strength dictated by the symposiarch, but didn’t reach extremes of drunkenness. Taking part in various forms of sympotic activity and sharing the same eating and drinking rituals the guests attempted to maintain social cohesion and group solidarity. 52
On the proper behaviour at the table or the code of the sympotic ethics in the Banquet of Philoxenus on the background of the Greek literary tradition
Keywords: Philoxenus; deipnon; symposium; sympotic ritual; entertainment; proper behaviour; balance